Morphology of nutrient storage cells in the gonadal area of the Pacific oyster, Crassostrea gigas (Thunberg, 1793). (February 2019) - Yurchenko, Olga V.; Kalachev, Alexander V.
Highlights: Oysters accumulate glycogen and lipids within a single cell type, the VCT-cells. VCT-cells are morphologically similar to brown adipocytes of mammals. The amount of glycogen and lipids varies between VCT-cells within a cluster. Myoepithelial cells surround both gonadal acini and clusters of VCT-cells. Abstract: Successful gametogenesis in invertebrates is tightly associated with functioning of specific nutrient-storing cells. In oysters, cells of vesicular connective tissue (VCT-cells), also referred to as storage cells, which form a meshwork around gonadal acini, are the major population of cells that accumulate and provide nutrients for developing gametes. During the annual reproductive cycle, populations of developing germ cells and VCT-cells demonstrate the inversely proportional size dynamics: the larger the acini, the smaller the VCT-cells. In the present study, the morphology of VCT-cells in the Pacific oyster, Crassostrea gigas, at the active gametogenesis stage of reproductive cycle has been studied using light and transmission electron microscopy. At this stage, VCT-cells are big, irregularly shaped cells containing large nucleus with a single large nucleolus. The cytoplasm contains weakly developed endoplasmic reticulum, mitochondria in the perinuclear area and at periphery of the cell, numerous lipid droplets, and glycogen particles. Ultrastructure of VCT-cells is similar to the organization of brown adipocytes in mammals. The surface of cells has numerous cytoplasmic processes that are presumably associated with the transport function and provide close interaction with adjacent cells. The spatial relationship between VCT-cells and myoepithelial elements of the gonad area is demonstrated and discussed.